Machine Optimization of SNK HF Fabrication Plant in PT. Komatsu Indonesia with FMEA Method and Overall Equipment Effectiveness (OEE) - Melya Dyanasari Sebayang; Bantu Hotsan Manullang; Argarino, Titus (Talenta Publisher, 2021)
The effectiveness of a machine is an important thing in the production process; the losses that arise can cause time losses and hamper the process, especially in vital production facilities. The SNK HF machine is a machine with category A or critical with the highest damage occurring throughout 2019–2020. Analysis of the condition of the machine’s effectiveness in this study was done by using the overall equipment effectiveness (OEE) method, namely by knowing the conditions of availability, performance and quality. The results of the OEE analysis are followed by a failure mode effect analysis (FMEA) to overcome the problems that occur. The condition of machine damage and the availability of machine parts are the factors that most affect the decrease in the effectiveness of the SNK HF machine.